Applying active force control with fuzzy self-tuning PID to improve the performance of an antilock braking system - Al-Mola, Mohammed Hussin Ahmed; Salim, Mohd Azli; Mailah, Musa (Universiti Malaysia Perlis, 2021)
One of the safety devices in ground vehicles is anti-lock brake system (ABS) that works to prevent wheel lockup when sudden braking happen. The existence of this system in the vehicles gives it the power to control the pressure level in order to preserve the stability of the wheel slip and hence of the vehicle. Though, the ABS displays vigorous nonlinear behavior at any point, the vehicle fitted with the controller might have a propensity for instability. This paper presents a new robust control approach based on an active force control (AFC) loop coupled with a self-tuning fuzzy logic (FL) based proportional-integralderivative (PID) control scheme for the effective performance of the proposed ABS through the simulation analysis. To achieve a satisfactory result in the controller, both the FLPID and FLPID-AFC schemes are simulated and compared. The results is clear that, relative to the FLPID with the AFC scheme displays a quicker and better response under different operating conditions and loads compare with the FLPID controller. The implementation of the AFC-based controller into the ABS offers robust and stable performance that is capable of being deployed on the ground vehicle in a real-time and workable system